2011
DOI: 10.1099/jmm.0.024596-0
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream infection caused by Acinetobacter junii in a patient with acute lymphoblastic leukaemia after allogenic haematopoietic cell transplantation

Abstract: Acinetobacter junii is a rare human pathogen associated with bacteraemia in neonates and paediatric oncology patients. We present a case of A. junii causing bacteraemia in an adult transplant patient with leukaemia. The correct identification of Acinetobacter species can highlight the clinical significance of the different species of this genus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
0
11
0
2
Order By: Relevance
“…It has been reported to be associated with septicaemia in neonates and paediatric oncology patients, 36–39 and with meningitis, 40 refractory peritonitis, 41 ocular infection 42 and bloodstream infections in patients with acute lymphoblastic leukemia. 43 Wang et al. 44 reported that A. pittii causes hospital-acquired pneumonia and Wisplinghoff et al.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to be associated with septicaemia in neonates and paediatric oncology patients, 36–39 and with meningitis, 40 refractory peritonitis, 41 ocular infection 42 and bloodstream infections in patients with acute lymphoblastic leukemia. 43 Wang et al. 44 reported that A. pittii causes hospital-acquired pneumonia and Wisplinghoff et al.…”
Section: Discussionmentioning
confidence: 99%
“…Acinetobacter junii enfeksiyonlarının neonatal dönemde (12), pediatrik onkolojik hastalarda (13), yetişkin immün yetmezliği olan hastalarda septisemi nedeni (14,15) ve korneal perforasyon (16) nedeni olabileceği rapor edilmiştir. Kappstein ve ark.…”
Section: Discussionunclassified
“…Prashanth ve ark. (16) (15) ampirik tedavi olarak piperasilin/tazobaktam ile tedavi edilen bir hastada bu antimikrobiyal ajana duyarlı olmasına rağmen Acinetobacter junii'nin neden olduğu bir kan dolaşımı enfeksiyonu geliştiğini gözlemlemişlerdir. Ancak bu duruma bakteriyemi epizodu sırasında hastanın almakta olduğu kortikosteroid tedavisinin de neden olabileceği belirtilmiştir.…”
Section: Discussionunclassified
“…The metal content ( 24 Mg, 27 Al, 47 Ti, 53 Cr, 55 Mn, 56 Fe, 57 Fe, 59 Co, 60 Ni, 63 Cu, 66 Zn, 90 Zr, 107 Ag, 111 Cd, 202 Hg, and 208 Pb) of October 2017 wastewater samples were measured on an inductively coupled plasma mass spectrometry (ICP-MS) (Agilent 7500). Wastewater samples were filtered through 0.22 µm Whatman™ Puradisc 23-mm syringe filters (GE Healthcare, Little Chalfort, Buckinhamshire, UK) prior to measurement.…”
Section: Icp-msmentioning
confidence: 99%
“…Among members of this genus, Acinetobacter junii has been shown to be an opportunistic pathogen causing disease in individuals with known malignancies, or in those who had received prior antibiotic treatment or invasive procedures. The symptoms of infection with A. junii include septicemia, bacteremia, empyema, peritonitis and keratitis [25][26][27]. Members of this genus have also been shown to facilitate uptake of ARGs from E. coli through horizontal gene transfer at higher rates than other studied bacteria [28].…”
Section: Introductionmentioning
confidence: 99%